2013
DOI: 10.1007/s10803-013-1983-8
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention for Sensory Difficulties in Children with Autism: A Randomized Trial

Abstract: This study evaluated a manualized intervention for sensory difficulties for children with autism, ages 4–8 years, using a randomized trial design. Diagnosis of autism was confirmed using gold standard measures. Results show that the children in the treatment group (n = 17) who received 30 sessions of the occupational therapy intervention scored significantly higher (p = 0.003, d = 1.2) on Goal Attainment Scales (primary outcome), and also scored significantly better on measures of caregiver assistance in self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 52 publications
6
133
1
9
Order By: Relevance
“…By contrast, hypocortisolism has also been identified in groups that are exposed to chronic stress, including children raised in Romanian orphanages (Gunnar & Vazquez, 2001) and other chronically stressful environments, such as being an ethnic minority (DeSantis et al, 2007). Based on the findings of this study, we hypothesize that children with SOR are constantly activating their stress response system, and given the information above, we raise awareness for the need to check for both hyper- Sensory Profile was not validated as an outcome measure (Schaaf et al, 2014) or subjected to testretest reliability examination in the user manual (Ohl et al, 2012). While there has been preliminary evidence of test-retest reliability in some subscores of the Sensory Profile (Ohl et al, 2012), further larger scale testing is required before it could be recommended as a reliable outcome measure (Schaaf et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…By contrast, hypocortisolism has also been identified in groups that are exposed to chronic stress, including children raised in Romanian orphanages (Gunnar & Vazquez, 2001) and other chronically stressful environments, such as being an ethnic minority (DeSantis et al, 2007). Based on the findings of this study, we hypothesize that children with SOR are constantly activating their stress response system, and given the information above, we raise awareness for the need to check for both hyper- Sensory Profile was not validated as an outcome measure (Schaaf et al, 2014) or subjected to testretest reliability examination in the user manual (Ohl et al, 2012). While there has been preliminary evidence of test-retest reliability in some subscores of the Sensory Profile (Ohl et al, 2012), further larger scale testing is required before it could be recommended as a reliable outcome measure (Schaaf et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Based on the findings of this study, we hypothesize that children with SOR are constantly activating their stress response system, and given the information above, we raise awareness for the need to check for both hyper- Sensory Profile was not validated as an outcome measure (Schaaf et al, 2014) or subjected to testretest reliability examination in the user manual (Ohl et al, 2012). While there has been preliminary evidence of test-retest reliability in some subscores of the Sensory Profile (Ohl et al, 2012), further larger scale testing is required before it could be recommended as a reliable outcome measure (Schaaf et al, 2014). At the time this study was designed and conducted, there Moreover, it may not be sensitive enough to detect meaningful changes at such a short interval period (4-week frequency), where the other studies used 8 to 10 weeks frequency between pre-and posttesting.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In SI, patients are exposed to particular sensory stimuli and are taught to become adaptable to these environmental stimuli, while they are required to perform tasks 21 . Preliminary research has, in fact, shown that SI techniques, particularly those that follow Ayres Sensory Integration ® Fidelity Measure 22 , can have a more influential effect on improving sensory processing and regulation, sensorimotor skills and social-emotional function than fine motor therapy or group therapy 23 , and such strategies have been shown to be not only effective, but also safe and practical 24 , In fact, one of the first randomised controlled trials that examined the effects of SI showed a significant increase in the goal attainment scale (an individualised measure for progress), as well as a significant improvement in self-maintenance and social behaviour in subjects who received the OT intervention compared with those who did not 25 .OT can introduce tasks that teach proper sensorimotor performance. Imagine, for example, in order to teach an individual with ASD how to multitask, a therapist might have the child hang from a swing, trapeze or rope ladder 26 and have the child simultaneously attempt to complete a jigsaw puzzle-an exercise that would be intended to improve one's tolerance for a sensory overload.…”
Section: Occupational Therapymentioning
confidence: 99%
“…All movements require constant change of posture and adjustment in the centre of gravity.4The reciprocal relations between posture and fine manual dexterity is evident in descriptions regarding the developmental sequence of acquiring movement control [6][7][8].…”
Section: Introductionmentioning
confidence: 99%